До питання про поняття сторін як основних учасників цивільного процесу - Васильєва-Шаламова, Жанна Віталіївна; Васильева-Шаламова, Жанна Витальевна; Vasil'eva-Shalamova, Zhanna; Гуменюк, Костянтин Петрович; Гуменюк, Константин Петрович; Gumenjuk, Konstantin (Одеса : Юрид. л-ра, 2014)
The article draws attention of scholars to the lack of legal definitions of parties as the main participants in the civil process. Analysis of various scientific approaches to the definition of the parties as the main participants of civil procedure has been carried out. The author has come up with particular suggestions to the improvement of the aforementioned concept for forthcoming stipulation.
Васильєва-Шаламова Ж. В. До питання про поняття сторін як основних учасників цивільного процесу / Ж. В. Васильєва-Шаламова, К. П. Гуменюк // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 205-211.
Keywords: сторони; суб’єкти цивільних процесуальних правовідносин; поняття сторін; характерні ознаки сторін; стороны; субъекты гражданских процессуальных правоотношений; понятие сторон; характерные признаки сторон; parties; parties to civil legal proceedings; notion of parties; characterizing features of the parties